Developmental lead exposure: behavioral alterations in the short and long term - Moreira, E. G.; Vassilieff, I; Vassilieff, V. S. (Elsevier B.V., 2001)
Wistar dams were exposed to 500 ppm of Pb, as Ph acetate, or 660 ppm Na acetate in drinking water during pregnancy and lactation. Male pups at 23 (weaned) or 70 days (adult) of age were submitted to behavioral evaluation and Pb determination. The behaviors evaluated were: locomotor activity (open-field test), motor coordination (rotarod test), exploratory behavior (holeboard test), anxiety (elevated plus maze and social interaction tests), and learning and memory (shuttle box). Ph levels were measured in the blood and cerebral regions (hippocampus and striatum) of dams and pups. The results of the present report demonstrated that exposure to Ph during pregnancy and lactation induces in weaned pups hyperactivity, decreased exploratory behavior, and impairment of learning and memory. These alterations were observed at blood Ph levels in the range that may be attained in children chronically exposed to low levels of Pb (21 +/- 3 mug/dl). Regarding adults, the results demonstrated that the regimen of exposure adopted induces anxiety in these animals at nondetectable blood Ph levels. (C) 2001 Elsevier B.V. All rights reserved.
Keywords: lead; developmental lead exposure; lead toxicity; blood lead; brain lead